231k views
1 vote
Solve each system by elimination: -6x-y=-17 -2x-3y=-3

2 Answers

2 votes

Answer:

Point Form: ( 3 , − 1 )

Equation Form: x = 3 , y = − 1

Explanation:

Add the equations in order to solve for the first variable. Plug this value into the other equations in order to solve for the remaining variables.

User StatsStudent
by
6.2k points
2 votes

Answer:

(3, -1)

Explanation:

Multiply the 2nd equation (-2x-3y=-3) times -3 to eliminate x

Subtract/add the other terms -y + 9y and -17 + 9

Then divide 8y = 8

y= -1

Substitute y in the other equation

x = 3

(3, -1)

User Nurabha
by
6.0k points